2000
DOI: 10.1002/pc.10237
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the roles of two shrinkage‐controlled low‐profile additives in water aging of polyster resin–glass fiber composites

Abstract: A model previously formulated or water sorption in polyester resin‐glass fiber composites has been applied to the kinetic analysis of experimental data for two composites containing a hydrolysable (polyvinyl acetate‐PVAc) and a non‐hydrolyzable (polystyrene‐PS) shrinkage‐controlling low‐profile additive (LPA) respectively. It was found that the equilibrium water uptake in the composites and their unreinforced matrix is not drastically affected by the type of LPA. The kinetics of water sorption in the composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Concerning the reliability of bending tests and acknowledging that the standard short beam and flexural tests will remain the most used by the pultrusion industry, their interpretation needs to be adjusted depending on the material under investigation. The old ASTM D2344 standard for the short beam shear test [7] advises for an L/h ratio of 5 for glass fiber reinforcement and the newest approval [3] advises an L/h ratio of 4. This investigation shows that unidirectional pultruded composites fail by shear at lower loads than those based on the standard requirement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the reliability of bending tests and acknowledging that the standard short beam and flexural tests will remain the most used by the pultrusion industry, their interpretation needs to be adjusted depending on the material under investigation. The old ASTM D2344 standard for the short beam shear test [7] advises for an L/h ratio of 5 for glass fiber reinforcement and the newest approval [3] advises an L/h ratio of 4. This investigation shows that unidirectional pultruded composites fail by shear at lower loads than those based on the standard requirement.…”
Section: Resultsmentioning
confidence: 99%
“…Low profile additives (LPA) are thermoplastics partially compatible with unsaturated polyester resins (UPE) before the cure. LPA are added to unsaturated polyesters in order to control the shrinkage during the cure and hence improve the surface aspect [2,3]. Such characteristics are mostly required in the automotive industry where the surface aspects are of primary importance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the plasticization effect of water on PVAc has been reported for polymeric composites of PVAc and polystyrene (27).…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Moreover, the additive loss by migration leads to a reduction in the lifetime of the material. In literature, many authors reported studies on hydrothermal ageing of polyesters and polyamides, [1][2][3][4][5] however, few publication were dedicated to poly(vinyl chloride) (PVC). [6 -8] As well known, PVC is a less hydrophilic material and an absorption of a small amount of water may result in dielectrical properties deterioration.…”
Section: Introductionmentioning
confidence: 99%